William Gillies - modernism and nation in British art - McPherson, Andrew (Edinburgh University Press, 2023)
"Shows how European modernism inspired Gillies to engage with universal issues of purpose, meaning and fate to produce idiomatic and unique works. Reveals an artist who informs and challenges the constitutive narratives of modernism in Britain. Shows how competition between Scottish and English nationalisms has shrouded Gillies in myth. Combines social, political, cultural, and art history to explain the emergence of Gillies as artist and modernist. Examines new biographical evidence on questions of sexuality, gender, mental and physical health, scepticism and faith. Providing new evidence on the life and times of this Scottish painter, Andrew McPherson shows Gillies to be a modernist thinker. Presenting paintings never seen before, he reappraises his creative output, including the relationship of portraiture to still life, placing him firmly within not only a Scottish context but a British and European one, too. McPherson has been researching the life, times and works of William Gillies for over twenty years. He has rethought the formative influence of his art of two World Wars, gender inequalities and the modernist crisis of meaning and belief"--Publisher's description
Keywords: Gillies, William George -- 1898-1973; Geschichte 1901-1960; Ölmalerei